Washington Irving. - Leary, Lewis, 1906-1990 (University of Minnesota pamphlets on American writers, 1963)
With quick eye, ready tongue, and alert recognition of absurdities, Washington Irving sits quietly at both ends of the American literary spectrum -- an expatriate seeking reverently in Europe for sources of culture, but most effective in realizing American characters enmeshed in American ideals; and at the same time a native myth-maker who wove indigenous lore into comic tales which became fables. His country's first, but not her best, romantic historian; an early, but unsatisfying, impressionistic biographer; an exotic local colorist; a mildly boisterous, thigh-slapping, sidesplitting rural humorist;, a comic realist, a caricaturist. - p. 44.